Features of civil regulation on the territory of the International financial center «Astana» - Batyrbekova, Д.С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
The work is devoted to the analysis of legal norms of the current law of the International Financial Center “Astana» and the current law of the Republic of Kazakhstan, regulating civil relations on the territory of the International Financial Center «Astana». The relevance of the work is confirmed by the fact that the new Concept of the legal policy of the Republic of Kazakhstan until 2030 pays special attention to the development of the civil law industry, coupled with an emphasis on creating a favorable investment climate. The purpose of this work is to analyze the current law of the Center, adopted acts of the International Financial Center «Astana» in the field of civil law relations. In addition, the article discusses the issues of the action of the highest legal force of the Constitution of the Republic of Kazakhstan on the territory of the Center. The author identified two approaches: the first is the absoluteness of the constitutional postulate of the highest legal force of the Constitution on the territory of the Center. The second approach is to be somewhat limited, taking into account the special legal regime of the Center. Particular emphasis is placed on the operation of the acts of the Center in the field of civil legal relations. Based on the adopted acts of the Center, the author analyzes the possibility of applying collaborations of legal norms, including the norms of statutory and case law of England and Wales to regulate a specific legal relationship. At the same time, we believe that for another type of legal relationship, such an application is not provided for by the acts of the Center.